Osteochondral and Ligament Injury Patterns in Ankle Fractures: A Prospective Multi-Center Study. Issue 2 (April 2022) - Carreira, Dominic S.; Shaw, Daniel B.; Harris, Thomas G.; McCullough, Kirk A.; Kreulen, Christopher D.; Martin, RobRoy; Acevedo, Jorge I.
Category: Ankle; Arthroscopy; Sports; Trauma; Other Introduction/Purpose: When treating ankle fractures, the presence of talar osteochondral lesions and the extent of ligamentous injury are associated with the severity of injury. The Danis-Weber classification system has been used to predict potential ligament damage. The purpose of this study is to validate the ligament injury patterns that have been proposed to occur with the Danis-Weber Classification and identify the cartilage injury pattern that occurs on the talus with each fracture type. Methods: A prospective, multi-center foot and ankle arthroscopy registry was queried for patients who underwent arthroscopic treatment of ankle fractures. Preoperative and intraoperative findings were noted, including the Danis-Weber fracture classification, presence and location of osteochondral damage, and unstable deltoid, and/or syndesmotic ligaments. Kendall's tau-b, a nonparametric correlation coefficient for ordinal variables, was used to measure the strength and direction of association between Weber fracture type and the presence of a syndesmotic injury, deltoid ligament tear, medial malleolus fracture, or osteochondral lesion. The locations of osteochondral damage were compared as percentages. Results: 73 subjects were prospectively collected as part of a multicenter ankle arthroscopy database. Average subject age was 43 years (SD = 17) with 59% female and 41% male. A significant association between the presence of a syndesmotic injury and fracture type was identified, with syndesmotic injuries more likely occurring with a Weber C fracture (p < 0.0005). A significant association was not identified between Weber classification and a deltoid tear or medial malleolus fracture (p = 0.47, p = 0.79). Location of the talar osteochondral lesions were as follows: 22% medial-anterior, 22% lateral-anterior, 22% lateral-central, 17% central-anterior, 9% medial-central, 4% later-posterior, 4% central. There was no significant association identified between Weber classification and the location of the osteochondral injury (p = 0.99). Conclusion: Concurrent injuries with syndesmotic disruption, deltoid ligament tears, medial malleolus fractures, and osteochondral lesions have been proposed to be associated with Weber C ankle fractures. However, in this multicenter study, only syndesmotic injuries were associated with the Weber C classification. This study found similar rates of medial malleolus fractures and osteochondral lesions in Weber B and C type fractures.